Egy sikertelen kísérlet: A nyugati jogtörténeti kutatások kezdete Japánban - Sato, Dan (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
This paper sketches out the early phase of the academic discipline ‘Western (or European) Legal History’ in Japan through the case of Satoshi Nishimoto, who was one of the first scholars to specialise in this discipline. Nishimoto studied in Germany during the National Socialists era. Following his return to Japan, he published a series of papers which were influenced by national socialistic ideology. Due to the fact that the subjects of these papers seemed to bare no relation to European legal history, he was unable to gain much recognition as a legal historian. However, it seems that these papers were an attempt to introduce the research methodology prevalent in Germany at the time of his studies, namely that of legal history as either serving politics or needing to be combined with geopolitics. In any case, his attempt ended in failure.